(untitled) (Annals of Medical Research, 2021)
Aim: It is still controversial whether or not testicular fixation is required for undescended testes surgery. In this study, we aimed to compare the results of the patients with undescended testis in a single center, who underwent orchiopexy with or without transfixation suture.Material and Methods: The medical records of the patients with undescended testes who were operated at our tertiary pediatric surgery department were retrospectively analyzed between July 2015 and November 2018. Patients were divided into two groups as fixation performed (Group 1) and not performed (Group 2). Group 1 included n=30 patients (40 testes) and Group 2 included n=41 patients (49 testes). The age of the patients, type of undescended testis, surgical technique and complication rates were determinedResults: The mean age of the patients was 37.2 (12-104) months in Group 1 and 41.2 (12-110) months in Group 2. In both groups, complications such as recurrence, testicular atrophy, testis torsion, and hernia or hydrocele formation were not observed. One patient in Group 2 developed wound infection, which was recovered with antibiotic treatment.Conclusion: As a result of the short-term follow-up of our study, there was no clinically significant difference between the two groups. Therefore, we recommend the use of other techniques that do not include parenchymal suture fixation during orchiopexy, and avoiding the routine use of testicular parenchymal sutures if possible. Keywords: Undescended testis; orchiopexy; fixation.